2012
DOI: 10.3390/catal2010139
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation Catalysts for Elemental Mercury in Flue Gases—A Review

Abstract: Abstract:The removal of mercury from flue gases in scrubbers is greatly facilitated if the mercury is present as water-soluble oxidized species. Therefore, increased mercury oxidation upstream of scrubber devices will improve overall mercury removal. For this purpose heterogeneous catalysts have recently attracted a great deal of interest. Selective catalytic reduction (SCR), noble metal and transition metal oxide based catalysts have been investigated at both the laboratory and plant scale with this objective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(44 citation statements)
references
References 83 publications
0
38
0
Order By: Relevance
“…Au and V 2 O 5 activesites are known to adsorb mercury on their surface [17,29]. Surface experimental studies conducted on the SCR catalysts suggested that V 2 O 5 -active sites oxidize elemental mercury via Langmuir-Hinshelwood mechanism with both adsorbed Hg el and HCl species reacting to form weakly adsorbed HgCl 2 which is subsequently desorbed from the catalyst surface [7].…”
Section: Possible Mechanistic Pathways For Mercury Oxidation On Au/timentioning
confidence: 99%
See 2 more Smart Citations
“…Au and V 2 O 5 activesites are known to adsorb mercury on their surface [17,29]. Surface experimental studies conducted on the SCR catalysts suggested that V 2 O 5 -active sites oxidize elemental mercury via Langmuir-Hinshelwood mechanism with both adsorbed Hg el and HCl species reacting to form weakly adsorbed HgCl 2 which is subsequently desorbed from the catalyst surface [7].…”
Section: Possible Mechanistic Pathways For Mercury Oxidation On Au/timentioning
confidence: 99%
“…Ammonia, to a certain degree, and in a very pronounced manner the simultaneous presence of NH 3 and NO, will cause reduced mercury oxidation activity of SCR-DeNOx catalysts [19,21]. Due to these inhibitive effects, mercury oxidation takes place mostly at the outlet of an SCR reactor after most of NH 3 has been used up in the DeNOx reaction [7,22].…”
Section: Hg Co-oxidation In Scr Denox Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, considering that mercury brain content ranging from 2.5 to 10 M has already been associated to delayed psychomotor development in cases of exposure to minimal amounts of mercury poisoning, it was recently suggested that exposure to levels ten times lower could also lead to genotoxic consequences on the developing central nervous system, pointing to the need of reviewing the tolerance values published in 1990 by the WHO [67].…”
Section: Mercury Speciation and Its Transportationmentioning
confidence: 99%
“…In recent years, with the rapid development of global industrialization, environmental problems caused by fossil fuel combustion are becoming more and more serious [1][2][3][4][5]. As possible alternatives of fossil fuel, biomass resources-one of the renewable energy sources-has attracted much attention [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%